PEMETAAN RISET GLOBAL TENTANG PAJAK DIGITAL: ANALISIS BIBLIOMETRIK BERDASARKAN DATA SCOPUS - Sulastri, Sulastri; Santoso, Rachmat Agus; Fitriana, Fitriana (Politeknik Negeri Ambon, 2025)
Introduction: The development of the digital economy has led to the emergence of an urgency to design a new taxation approach that can accommodate digital economy activities reasonably and effectively, thus giving rise to the concept of digital tax. This research aims to map the global literature related to digital taxation, identify key topics, and find novel opportunities for future research. Methods: The method used was a bibliometric analysis with the VOSviewer application on 49 Scopus-indexed articles for 2018–2025. Results: The mapping results show that the theme of